ANALYTICAL APPROACH TO THE CONCEPT OF CULINARY EXPERIENCE IN TOURISM: Identifying Factors that Shape Memorable Experience - Istifania, Risna; Salsabila, Shofia; Utari, Sri; Rahayu, Hanifah Purwa; Floresta, Dwi Laila; Setiyorini, Heri Puspito Diyah (Faculty of Islamic Economic and Business - Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Abstract: This research explores the core elements of a memorable culinary tourism experience, highlighting the relationship between food, memory, and traveler behavior. Using a qualitative memory-work method developed by Haug (1987), this study involved 56 respondents, predominantly female (85.71%) aged 21-25 years (87.50%), and residing in West Java (70.36%). Respondents provided insights into their culinary preferences, factors contributing to memorable experiences, and personal stories through open-ended questions. This research employs Memorable Tourism Experience (MTE) theory and culinary tourism experience concepts to analyze the data. Key findings suggest that memorable culinary experiences are shaped by the uniqueness of food and beverages, the ambience of the location, the presence of companions, special moments, and other touristic elements such as service quality and price. These elements contribute to travelers' emotional connections and influence future destination preferences. This research provides a comprehensive understanding of how culinary tourism can drive loyalty and enrich the travel experience. Keywords: culinary tourism; memorable experiences; food and memory Abstrak: Penelitian ini mengeksplorasi elemen inti dari pengalaman wisata kuliner yang berkesan, dengan menyoroti hubungan antara makanan, memori, dan perilaku wisatawan. Metode yang digunakan pada penelitian ini adalah kualitatif memory-work yang dikembangkan oleh Haug (1987), penelitian ini melibatkan 56 responden yang sebagian besar adalah perempuan (85,71%) dengan rentang usia 21-25 tahun (87,50%), dan berdomisili di Jawa Barat (70,36%). Responden memberikan wawasan tentang preferensi kuliner mereka, faktor yang berkontribusi pada pengalaman berkesan, dan cerita pribadi melalui pertanyaan terbuka. Penelitian ini menggunakan teori Memorable Tourism Experience (MTE) dan konsep culinary tourism experience untuk menganalisis data. Temuan utama menunjukkan bahwa pengalaman kuliner yang berkesan dibentuk oleh keunikan makanan dan minuman, suasana lokasi, kehadiran pendamping, momen spesial, dan elemen turistik lainnya seperti kualitas layanan dan harga. Elemen-elemen ini berkontribusi pada koneksi emosional wisatawan dan memengaruhi preferensi destinasi di masa depan. Penelitian ini memberikan pemahaman komprehensif tentang bagaimana wisata kuliner dapat mendorong loyalitas dan memperkaya pengalaman wisata. Kata Kunci: wisata kuliner; pengalaman; makanan dan kenangan